Evaluasi Stabilitas Lereng Dengan Metode Limit Equilibrium pada Sungai Waridin - Kurniawan, Andri; Wahyu Adhi, Bagas; Pamungkas, Hannung; Qomaruddin, Mochammad (Universitas Veteran Bangun Nusantara, 2025)
Rivers play an important role in improving the welfare and quality of life of the Indonesian people. In addition, rivers can also cause flooding. The Waridin River is one of the rivers in the Kendal regency area. Flooding is an event where inundation occurs in a flat area around the river due to the overflow of water that the river cannot accommodate. To overcome the flood problem, the addition of parapets and the normalization of the river were carried out. For this reason, it is necessary to analyze the slope stability of the Waridin river from the excisiting conditions, design and construction conditions by paying attention to 3 (three) modeling conditions. The method used in this analysis is the Limit Equilibrium method, which utilizes software, specifically Geostudio, through the SLOPE/W menu. The analysis was carried out on existing conditions, planning, and construction. This analysis was carried out under normal conditions, earthquakes, and rapids. The results of the existing analysis were obtained that in the condition of the combination of earthquakes, the slope stability was below the safe factor, namely 1.02 < 1.2. sendang in other conditions tends to be safe. In the planning analysis by combining normalization and the addition of parapets with a 3-meter mini pile foundation, the results of all analysis conditions exceeded the value of the safety factor. Because at the time of construction a landslide occurred, a back analysis was carried out where the results of the back analysis were added reinforcement to the foot of the river slope with a mini pile of 4 meters with a distance of 1 meter each associated with the frame beams. The analysis results obtained show that it is safe for all implementation conditions.